Enhancing Job Performance in the Hospitality Sector: Exploring the Role of Employee Engagement, Multitasking, Organizational Culture, and Recruiting Practices - Dalkhjav, Battsetseg; Munkhuu, Bilegsaikhan; Sukhragchaa, Amarjargal Sukhragchaa (Journal of Tourism, Sustainability and Well-being, 2024)
In a time marked by the urgent need to enhance the quality and productivity of Mongolia’s hospitality sector, this research aimed to boost job performance through increased employee engagement and the identification of influencing factors. Initially, core indicators such as increased employee engagement, multitasking jobs, and organizational culture were analyzed to understand their individual and collective impacts on job performance. The study delved into the multitasking nature of hospitality employment where employees must juggle multiple tasks simultaneously, and the fluctuating nature of organizational culture aligns with Mongolia’s seasonal attributes. Given the industry’s characteristics and workforce instability, the research conducted a comparative analysis focusing on human resource recruiting practice as the controlling variable. A total of 155 hospitality industry employees participated in this primary study on employee engagement within the sector. The study’s finding revealed that multitasking jobs and organizational culture positively impact job performance by enhancing employee engagement. Additionally, the research highlighted variations in employee engagement and job performance based on specific human resource recruitment methods employed initially.